Local government preferences, individual needs, and the allocation of social assistance - Audun Langørgen; Dag Rønningen (Statistics Norway, Research Department, 2004)
Governments that pursue welfare and equalization goals frequently target cash transfers to individuals that suffer from limited economic opportunities and poverty. To achieve the desired allocation of welfare benefits, evaluation of individual needs is thus required. However, the political support for redistribution may vary across communities and governments, depending on ideology of the dominant political parties, political power of interest groups, and geographic, cultural and social diversity within the community. The purpose of this paper is to analyze the allocation of social assistance to individuals by local governments in Norway. Available data on individual characteristics as well as variables at the municipal level allow us to separate the impact of individual needs from the impact of different local government treatment. The results show that priorities across individuals are affected by characteristics that capture individual economic opportunities and needs, whereas theories that suggest different priorities between local governments find little support.
Keywords: D31; H72; 330; Social assistance; Income distribution; Local public finance